The Role of NLR-related Protein 3 Inflammasome in Host Defense and Inflammatory Diseases - Yang, Chul-Su; Shin, Dong-Min; Jo, Eun-Kyeong (International neurourology journal, 2012)
Among a number of innate receptors, the nucleotide-binding domain leucine-rich repeat containing (NLR) nucleotide oligomerization domain (NOD)-like receptor families are involved in the recognition of cytosolic pathogen- or danger-associated molecules. Activation of these specific sets of receptors leads to the assembly of a multiprotein complex, the inflammasome, leading to the activation of caspase-1 and maturation of the cytokines interleukin (IL)-1β, IL-18, and IL-33. Among NLRs, NLR-related protein 3 (NLRP3) is one of the best-characterized receptors that activates the inflammasome. There is no doubt that NLRP3 inflammasome activation is important for host defense and effective pathogen clearance against fungal, bacterial, and viral infection. In addition, mounting evidence indicates that the NLRP3 inflammasome plays a role in a variety of inflammatory diseases, including gout, atherosclerosis, and type II diabetes, as well as under conditions of cellular stress or injury. Here, we review recent advances in our understanding of the role of the NLRP3 inflammasome in host defense and various inflammatory diseases.